THE USE OF APHORISMS IN THE EDUCATIONAL PROCESS: THEIR ROLE IN ENHANCING TEACHING AND LEARNING - Jo’raqulova Hurmatoy, (TADQIQOTLAR, 2025)
Annotation:This  article  explores  the  role  of  aphorisms  in  the  educational process, focusing on their pedagogical significance and cultural value. Aphorisms are examined as concise forms of wisdom that not only enrich classroom instruction but also  foster  critical  thinking  and  moral  development  among  learners.  The  study highlights how aphorisms from Uzbek and English traditions reflect universal human values  while  preserving  cultural  identity.  It  further  emphasizes  the  potential  of aphorisms  to  motivate  students,  stimulate  discussion,  and  connect  theoretical knowledge with real-life experiences. The article argues that incorporating aphorisms into teaching can enhance both intellectual growth and ethical education, making them a valuable resource for modern pedagogy.